(untitled) (Historia, 2021)
Wyndham, the epitome of a nineteenth-century English country gentleman, migrated to South Africa in 1901. After serving Milner as an unpaid private secretary, he helped re-established the horse industry after the devastation of the Anglo-Boer War and entered South African politics first as a Transvaal Progressive and after 1910 as a Unionist. This article places Wyndham in his setting, explores his extraordinary background and analyses the extent and importance of his social network. Family connections saw to a job on Milner's staff and inherited money established his later farming and political career. Yet, an anachronism in a changing South Africa, he returned permanently to Britain in 1930, which, as he soon realised, had changed too.